Shoulder Joint Flexibility of Pointer, Middle, and Shooter Players in Petanque Athletes, State University of Jakarta - Yuliasih; Nadya Dwi Oktafiranda; Ramdan Pelana; Ela Yuliana; Sri Indah Ihsani (Jurnal Pendidikan Jasmani (JPJ), 2023)
Pétanque sport is a sport of dexterity in throwing the blindest ball from the iron by getting the target ball closer (pointing) and keeping the opponent's ball away (shooting), and both feet are in a circle. The purpose of this study was to determine the flexibility of the shoulder joint in UNJ pétanque athletes seen from the position of the players, namely pointer, middle, and shooter, and measurements were carried out in the flexion and extension positions. The method used in this study is to use a descriptive method with a measurement technique that measures the flexibility of the shoulder joint. The population in this study was UNJ pétanque players totaling 30 people with a sampling technique namely with accidental sampling technique totaling 24 people. Data collection technique by measuring the flexibility of the shoulder joint using a goniometer. The research was conducted on the 2nd floor of the Biomechanics Lab of GOR UNJ. The results of the study on flexion measurements at the position of pointer players are 187.78°; Middle 201.67° and Shooter 187.78°. While the extension measurement at the pointer position is 83.33°; Middle 84.17° and Shooter 84.44°. The conclusion of this study was obtained Flexion measurements on pointers, middles, and shooters are all in the very good category. Normally 0-180°. The extension measurements on the pointer, middle, and shooter are all in the excellent category. Normally 0-60°. So, pointer, middle, and shooter players have the same physical condition that does not have a significant difference in shoulder joint flexibility.